2017
DOI: 10.1007/s11596-017-1774-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different concentrations and exposure time of sodium hypochlorite on the structural, compositional and mechanical properties of human dentin

Abstract: This study evaluated the effects of sodium hypochlorite (NaOCl) with different concentrations and exposure time on the structural, compositional and mechanical properties of human dentin in vitro. Sixty dentin slabs were obtained from freshly extracted premolars, randomly distributed into four groups (n=15), and treated with 1%, 5%, 10% NaOCl and distilled water (control group), respectively, for a total of 60 min. Attenuated total reflection infrared (ATR-IR) spectroscopy, Raman spectroscopy and X-ray diffrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 35 publications
4
33
0
Order By: Relevance
“…The action of loading produced a smear layer on the top surface, mainly composed of grinding debris containing small microcrystalline and organic particles. In order to examine the possible damaged top surface of the affected occlusal surfaces with SEM, the smear layer was removed carefully using NaOCl [Wang et al, 2017]. The specimens were exposed to a 2.5% NaOCl solution for 3 min during constant agitation with a brush.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…The action of loading produced a smear layer on the top surface, mainly composed of grinding debris containing small microcrystalline and organic particles. In order to examine the possible damaged top surface of the affected occlusal surfaces with SEM, the smear layer was removed carefully using NaOCl [Wang et al, 2017]. The specimens were exposed to a 2.5% NaOCl solution for 3 min during constant agitation with a brush.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…However, even single use of NaOCl at higher concentrations could affect the MH and FS values of root canal dentin in a time‐dependent manner . Wang et al reported that NaOCl had no significant effect on the inorganic components of dentin but caused a decrease in the organic components, which might influence the FS values of dentin. Considering that the organic component of dentin decreased with age, more prominent effects on FS values after NaOCl irrigation could be observed in young dentin than in aged dentin.…”
Section: Discussionmentioning
confidence: 92%
“…Besides ageing, root canal irrigants might also affect the structural and mechanical properties of dentin . Different studies, irrespective of age, showed that root canal irrigation solutions had a negative impact on the FS and MH of root dentin .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations